Machine Sensation Anthropomorphism and 'Natural' Interaction with Nonhumans - Leach, Tessa G. (New Metaphysics series, 2020)
Emphasising the alien qualities of anthropomorphic technologies, Machine Sensation makes a conscious effort to increase rather than decrease the tension between nonhuman and human experience. In a series of rigorously executed cases studies, including natural user interfaces, artificial intelligence as well as sex robots, Leach shows how object-oriented ontology enables one to insist upon the unhuman nature of technology while acknowledging its immense power and significance in human life. Machine Sensation meticulously engages OOO, Actor Network Theory, the philosophy of technology, cybernetics and posthumanism in innovative and gripping ways.